2011
DOI: 10.1371/journal.pone.0019044
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Interpersonal Psychotherapy and other Psychodynamic Therapies versus ‘Treatment as Usual’ in Patients with Major Depressive Disorder

Abstract: BackgroundMajor depressive disorder afflicts an estimated 17% of individuals during their lifetimes at tremendous suffering and costs. Interpersonal psychotherapy and other psychodynamic therapies may be effective interventions for major depressive disorder, but the effects have only had limited assessment in systematic reviews.Methods/Principal FindingsCochrane systematic review methodology with meta-analysis and trial sequential analysis of randomized trials comparing the effect of psychodynamic therapies ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 72 publications
0
17
0
1
Order By: Relevance
“…We also checked the references of earlier metaanalyses (3,(24)(25)(26) and a database of studies on psychological depression treatments (27).…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We also checked the references of earlier metaanalyses (3,(24)(25)(26) and a database of studies on psychological depression treatments (27).…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
“…Some focused on the effects of IPT for depression (3,(24)(25)(26), but none of these included trials published after 2010 (while 22 new trials have been subsequently published since [see below]); some focused on a small subsample of studies (24,25) or on narrow research topics, such as the comparison between IPT and care-as-usual (24) or direct comparisons between IPT and cognitive-behavioral therapy (CBT) (25). No meta-analysis has focused on IPT for disorders other than depression.…”
mentioning
confidence: 99%
“…In calculating our sample size we have used a ‘minimal relevant mean difference’ (MIREDIF) of five HDRS points between the two interventions. Former systematic reviews have shown much less differences in effects sizes between compared interventions for depression [44,51,52]. It could be argued that we have set our presumed MIREDIF unrealistically high.…”
Section: Discussionmentioning
confidence: 96%
“…This makes it possible to implement the interventions in clinical practice, and the two interventions can be assessed in future trials. Moreover, we have used the most commonly used outcome measure in trials assessing the effects of psychotherapeutic interventions for depression (HDRS) [28,37,44,51], as well as other clinically relevant outcome measures (e.g., quality of life, suicide attempts, suicides). The two treatments uses about the same resources, so economical considerations seem less important in the choice between the two.…”
Section: Discussionmentioning
confidence: 99%
“…Both the cognitive therapists and the mentalisation therapists were involved in developing the treatment manuals for the respective psychotherapeutic treatments, which might make the therapist enthusiasm and thoroughness similar in the two intervention groups. (3) We have used the most commonly used outcomes in trials assessing the effects of psychotherapeutic interventions for depression (ie, HDRS and BDI) 11 30 45 46. This makes it possible to relate our results to results from other trials examining the effects of interventions for depression.…”
Section: Discussionmentioning
confidence: 99%